Association of Epstein-Barr Virus Latent Membrane Protein 1 (LMP1) Gene Expression and Caspase Activity in Normal Nasopharyngeal Cell - Mohd Aminudin, Mustapha; Sim, Sai-Peng (Japan University of Health Sciences & Japan International Cultural Exchange Foundation, 2021)
Objective: To assess LMP1 gene expression-induced apoptosis in normal nasopharyngeal cells by measuring caspase activity. Material and Methods: LMP1 gene was subcloned into pTracer and pcDNA vector, producing pTracer-LMP1 and pcDNA- LMP1 expression plasmids. The plasmids were then transfected into normal nasopharyngeal cells. LMP1 gene expression-induced apoptosis was accessed by measuring Caspase activities using Caspase-Glo ® 3/7 Assay kit following the manufacturer's protocol. The luminescence intensity was measured by microplate reader. Association of LMP1 gene expression with caspase activation was analysed by independent Sample T test. Results: LMP1 gene expression in normal nasopharyngeal cells is significantly associated with higher caspase activity of apoptosis compare to the vector control with t(-2.142), p value of 0.03. Conclusion: Our results show that, there is association of LMP1 gene expression and caspase activity level in normal nasopharyngeal cell thus support that LMP1 gene expression is involved in apoptosis induction.